2007
DOI: 10.2105/ajph.2006.085662
|View full text |Cite
|
Sign up to set email alerts
|

Promises and Challenges of Faith-Based AIDS Care and Support in Mozambique

Abstract: Policy efforts to involve religious organizations in provision of HIV/AIDS-related assistance should take into account that organization's resources, institutional goals, and social characteristics.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
35
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 44 publications
(42 citation statements)
references
References 9 publications
7
35
0
Order By: Relevance
“…Results also indicate that regional HIV strategies need to proactively build the capacity of religious congregations and the schools they manage in regards to HIV transmission, prevention, and behavior modification (Agadjanian, 2005;Agadjanian & Sen, 2007;Pfeiffer, 2007). While beginning to occur in the rural Catholic schools of Central Mozambique (A. Gomes, personal communication, May 13, 2009), the need exists to focus on the leadership of these religious institutions because of the high level of mistrust generated from not being included in the initial national HIV prevention strategic planning initiatives (Pfeiffer, 2004).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Results also indicate that regional HIV strategies need to proactively build the capacity of religious congregations and the schools they manage in regards to HIV transmission, prevention, and behavior modification (Agadjanian, 2005;Agadjanian & Sen, 2007;Pfeiffer, 2007). While beginning to occur in the rural Catholic schools of Central Mozambique (A. Gomes, personal communication, May 13, 2009), the need exists to focus on the leadership of these religious institutions because of the high level of mistrust generated from not being included in the initial national HIV prevention strategic planning initiatives (Pfeiffer, 2004).…”
Section: Discussionmentioning
confidence: 99%
“…While beginning to occur in the rural Catholic schools of Central Mozambique (A. Gomes, personal communication, May 13, 2009), the need exists to focus on the leadership of these religious institutions because of the high level of mistrust generated from not being included in the initial national HIV prevention strategic planning initiatives (Pfeiffer, 2004). Future programs should also target religious congregations to build trust and develop HIV prevention strategies (CNCS, 2004;Green, 2003;Largarde et al, 2000;Pfeiffer, 2004) involving culturally relevant training related to cultural understandings of HIV transmission and prevention, not just transmitting generic information (Agadjanian, 2005;Agadjanian & Sen, 2007;Pfeiffer, 2007).…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, leaders from the Pentecostal churches and the Muslim groups expressed more severe messages about God's punishment as well as some stigmatising remarks about PLHIV. Agadjanian and Sen (2007) noted similar differences between mainstream and Pentecostal denominations in Mozambique. Despite different theologies and traditions, none of the religious organisations at the national or local levels included the promotion of condoms in their prevention messages although a few individuals broke away from their church or mosque in promoting them.…”
Section: Discussionmentioning
confidence: 65%
“…The scholarly literature on the role of ROs in mitigating the impact of HIV/AIDS is generally less celebratory, and studies have identified several problematic areas that are inherent to most ROs or vary in importance across different types of ROs (Agadjanian and Sen 2007, Casale et al 2010, Francis and Liverpool 2009, Haddad et al 2008, Trinitapoli 2009, Trinitapoli and Regnerus 2006). Thus it has been argued that ROs may contribute to HIV/AIDS-related stigma and discrimination (Keikelame et al 2010, Mbilinyi and Kaihula 2000.…”
Section: Background and Conceptual Approachmentioning
confidence: 99%